SOCIAL WORK FAILURE? THE ISSUES OF SOCIAL WORK DEVELOPMENTS IN POSTMODERNITY - Opatrný, Michal (Uniwersyteckie Czasopismo Socjologiczne, 2016)
This study deals with the current issues of social work mainly in the Czech and European contexts. It shows that the debate on social work crisis finds its roots of the crisis in social policy, and in structural, legislative and financial conditions it creates for social work. The study, therefore, suggests three questions that should be answered primarily by social work both as a practical profession and professional research, to be able to define its own professional interest.